Macrophage Colony Stimulating Factor as Predictive Marker of Osteoporosis in T2DM Patients - Hajer Mahmood, Eiman AA. Abass, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes mellitus and osteoporosis are two common medical disorders that are becoming more common as the population ages. T2DM patients have a higher fracture hazard, having a high BMD, which is primarily due to the raise hazard of falling. Macrophage colony-stimulating factor (M-CSF) is one of the hematopoietic growth factor family, and It plays an important function in fracture repair by attracting stem cells to the fracture site and influencing the production of hard calluses by promoting osteoclast genesis. Aims of study: The purpose of this research was to assess the blood level of macrophage colony-stimulating factor in Iraqi osteoporotic patients with and without type 2 diabetes. in addition, that M-CSF may be a predictive marker for osteoporosis in T2DM patients Subjects & Methods: This study was conducted between October 2021 to March 2022 in Medical City of Baghdad Teaching Hospital. The current study included 92 individuals (females and males) aged 40-65 years’ old, 67 of them are patients and 25 as a control. The lumber spine's bone mineral density was determined using dual energy x-ray absorptiometry (DEXA)scan to diagnose these patients. Patients divided into (20) person as T2DM patients, (27) person as osteoporosis patients, and (20) as osteoporosis patients with T2DM Results: The current study showed an important increase in serum M-CSF of osteoporosis patients with and without T2DM groups when compared with control, also, there was no significance increase in M-CSF level in T2DM patients comparing with control. Also, there was an important negative relation between M-CSF and bone mineral density (BMD) In osteoporosis patients, there was a substantial positive connection between M-CSF, FBS, and HbA1C. Conclusions: The current study demonstrated that serum macrophage colony-stimulating factor (M-CSF) levels was significantly elevated in osteoporosis patients with and without T2DM, Therefore, this parameter may be a diagnostic marker for osteoporotic patients. In addition, that diabetic patients may be prone to osteoporosis, and M-CSF may be a predictive biochemical marker for development of osteoporosis in type 2 diabetic patients. Keywords: Macrophage colony-stimulating factor, Osteoporosis, bone mineral density, Type 2 diabetes mellitus.